Leucoaférese terapêutica na laminite aguda induzida por oligofrutose emequinos - Odael Spadeto Junior (2017)
Previous studies from our group demonstrated that leukocyte infiltration precedes major structural damage of the lamellar tissue promoted by laminitis in equine hoof. With the hypothesis that the reduction of this migration using therapeutic leukapheresis results in clinical and histological improvement of the lamellar tissue of horses subjected to leukapheresis, this study had the following objectives: 1) to validate in horses the use of Falcão-Faleiros lamellotome, an instrument specifically designed to perform biopsies of the lamellar tissue of ungulate animals; 2) to describe a continuous flow leukapheresis technique and to verify its effects on blood leukocyte counts; 3) to evaluate the effect of removal of circulating leukocytes by means of a therapeutic leukapheresis protocol on the clinical and hematological variables and to identify the intensity of leukocyte infiltration and the degree hoof lamellar damage in horses with acute laminitis induced by oligofructose For the validation of the biopsy, nine adult horses subjected to the proposed technique were used. These horses were monitored clinically and radiographically for 60 days. For the leukapheresis experiments, twelve mares without previous history of lameness were used. Horses were randomly divided into two groups (n=6), control (CON) and treated (LEUCO). Sepsis and laminitis were induced by oral administration of oligofructose. Horses were monitored by clinical and laboratorial assessments. Serial biopsies were performed before and 12, 36 and 72h after induction. Twelve hours after induction the LEUCO animals were subjected to leukapheresis by continuous flow collection system with double venous access. The Falcão-Faleiros lamellotome was fully satisfactory, producing histological samples in adequate quantity and quality, without causing irreversible damage to the horses. It was also shown that the leukapheresis protocol reduced the concentration of circulating and infiltrated lamellar leukocytes, attenuating the signs of systemic inflammation and organic dysfunction, preventing deaths and alleviating lamellar lesions. In conclusion, the biopsy technique was effective in horses and the leukapheresis therapeutic protocol proved to be experimentally effective, demonstrating potential for clinical use.